A Fixed Point Approach to the Stability of the Cauchy Additive and Quadratic Type Functional Equation - Sun Sook Jin; Yang-Hi Lee (Journal of Applied Mathematics)
We investigate the stability of the functional equation 2𝑓(𝑥+𝑦)+𝑓(𝑥−𝑦)+𝑓(𝑦−𝑥)−3𝑓(𝑥)−𝑓(−𝑥)−3𝑓(𝑦)−𝑓(−𝑦)=0 by using the fixed point theory in the sense of Cădariu and Radu.